ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF ANTIPERSPIRANT COSMETIC PRODUCTS - Neli Ermenlieva; Emilia Georgieva; Minko Milev (Peytchinski Publishing, 2020)
In most deodorant products, antibacterial agents such as aluminum salts, alcohol and aromatic odor-masking agents, are used. Aim: The aim of the study is to evaluate the antimicrobial activity of antiperspirant cosmetic products consist of Aluminum Chlorohydrate and Alcohol to normal skin microflora and conditionally pathogenic bacteria, which can cause skin infections. Material and Methods: Antimicrobial activity was tested with strains S. epidermidis, S. aureus, C. albicans, S. pneumoniae and E. coli. The left half of media with microbial seeds was sprayed with antiperspirant cosmetic product at a distance of 15 cm for 3-4 seconds (Figures 1-5), and the other half was covered with wrapping paper. Results and Conclusion: Cosmetic products containing Aluminum Chlorohydrate demonstrate almost total inhibition of microbial growth. Complete suppression of the normal microbiota of the skin can lead to skin vulnerability in the armpit area. Antiperspirant cosmetic product containing Alcohol has antibacterial no inhibiting effects against S. epidermidis and demonstrated efficacy against S. pneumoniae and C. albicans.